Rare example of TICT based optical responses for the specific recognition of Cr3+ by a 2,2?:6?,2?-terpyridine derivative and demonstration of multiple logic operations - Mahato, Prasenjit; Saha, Sukdeb; Das, Amitava (Journal of Physical Chemistry C, 2012)
Chemosensor L showed a nonlinear fluorescence response on specific binding to Cr3+ ion in the presence of various alkali, alkaline-earth, transition, and lanthanide metal ions. A luminescence band with maxima at 512 nm for L was observed (λext = 330 nm) for a twisted intramolecular charge transfer (TICT) transition following antienergy gap law behavior. However, normal energy gap law behavior prevailed on formation of a new nonluminescent charge transfer complex, Mn+·L. For paramagnetic metal ions, paramagnetism induced luminescence quenching could have also contributed to this. A new switched on fluorescence response at λems of 356 nm (λext of 330 nm) was observed due to Franck–Condon charge transfer (FC-CT) transition only on the formation of a complex, (Cr3+)2·L. Spectral studies revealed a unique dynamic coordination behavior and migration of Cr3+ from the terpyridyl fragment to the NNMe2 center of L as a function of the varying concentration of another ion (Zn2+) and the subtle difference in the binding affinities of the terpyridyl moiety toward Cr3+ and Zn2+. Further, spectral responses of L toward Zn2+, different concentration of Cr3+, H+ and on subsequent addition of F– as different ionic inputs could be correlated well for demonstrating various basic and combinatorial circuits.